Exploiting non-linear scales in galaxy–galaxy lensing and galaxy clustering: A forecast for the dark energy survey. Issue 4 (4th January 2022) - Salcedo, Andrés N; Weinberg, David H; Wu, Hao-Yi; Wibking, Benjamin D
ABSTRACT: The combination of galaxy–galaxy lensing (GGL) and galaxy clustering is a powerful probe of low-redshift matter clustering, especially if it is extended to the non-linear regime. To this end, we use an N -body and halo occupation distribution (HOD) emulator method to model the redMaGiC sample of colour-selected passive galaxies in the Dark Energy Survey (DES), adding parameters that describe central galaxy incompleteness, galaxy assembly bias, and a scale-independent multiplicative lensing bias A lens . We use this emulator to forecast cosmological constraints attainable from the GGL surface density profile ΔΣ( rp ) and the projected galaxy correlation function wp, gg ( rp ) in the final (Year 6) DES data set over scales r_p=0.3\!-\!30.0 h^-1 Mpc . For a 3 per cent prior on A lens we forecast precisions of 1.9 per cent, 2.0 per cent, and 1.9 per cent on Ω m, σ8, and S_8 σ _8Ω _m^0.5, marginalized over all halo occupation distribution (HOD) parameters as well as A lens . Adding scales r_p=0.3\!-\!3.0 h^-1 Mpc improves the S 8 precision by a factor of ∼1.6 relative to a large scale (3.0\!-\!30.0 h^-1 Mpc ) analysis, equivalent to increasing the survey area by a factor of ∼2.6. Sharpening the A lens prior to 1 per cent further improves the S 8 precision to 1.1 per cent, and it amplifies the gain from including non-linear scales. Our emulator achieves per cent-level accuracy similar to the projected DES statistical uncertainties, demonstrating the feasibility of a fully non-linear analysis. Obtaining precise parameter constraints from multiple galaxy types and from measurements that span linear and non-linear clustering offers many opportunities for internal cross-checks, which can diagnose systematics and demonstrate the robustness of cosmological results.